2012
DOI: 10.1136/bjsports-2012-091050
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between ACL injuries and physical fitness in young competitive ski racers: a 10-year longitudinal study

Abstract: The risk of ACL injury was greater in female athletes. The findings suggest that core strength is a predominant critical factor for ACL injuries in young ski racers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
150
5
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 124 publications
(171 citation statements)
references
References 37 publications
12
150
5
1
Order By: Relevance
“…In this study all the female subjects had suffered ACL-injury [4,7,[16][17][18][19]. The present study reflects the consequences of an ACL injury in athletes, with results being consistent with those from other long-term studies on ACL injury in other sports [13,14,20].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In this study all the female subjects had suffered ACL-injury [4,7,[16][17][18][19]. The present study reflects the consequences of an ACL injury in athletes, with results being consistent with those from other long-term studies on ACL injury in other sports [13,14,20].…”
Section: Discussionsupporting
confidence: 87%
“…We were not able to estimate incidences due to multi-nationality and retrospective nature of the study. The literature is inconsistent when it comes to gender differences regarding the incidence of ACL injury in competitive alpine skiers but several studies showed results that ACL injuries occur in a younger age in female athletes than in their male counterparts [7,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the determination of leg dominance, subjects were asked which leg they would prefer to kick a ball. According to a study by Raschner et al [17], participants performed three one-leg isometric leg extensions on each leg. The greater trochanter, lateral intercondylar notch, and lateral malleolus were used as landmarks to ensure that a knee angle of 100° was reached (180° = fully extended knee).…”
Section: Isometric Leg Strength Testmentioning
confidence: 99%
“…The greater trochanter, lateral intercondylar notch, and lateral malleolus were used as landmarks to ensure that a knee angle of 100° was reached (180° = fully extended knee). The calculated strength parameters were the mean absolute leg force and the mean relative leg force which was got when dividing the absolute leg force by body weight [17].…”
Section: Isometric Leg Strength Testmentioning
confidence: 99%